2014
DOI: 10.1121/1.4863653
|View full text |Cite
|
Sign up to set email alerts
|

The perceptual assimilation of Korean obstruents by native Mandarin listeners

Abstract: The current study reports the results of a perception experiment in which 20 naive native Mandarin listeners classified and rated the goodness of Korean stops /p, t, k, p(h), t(h), k(h), p*, t*, k*/, affricates /tɕ, tɕ*, tɕ(h)/, and fricatives /s(h), s*/ in terms of Mandarin segmental categories. It was found that listeners were sensitive to the voice onset time dimension of Korean stops and the presence of aspiration in Korean affricates, but Korean lenis and aspirated obstruents were generally assimilated to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 34 publications
2
21
2
Order By: Relevance
“…This result for the NM group replicates Holliday (2014a), who found that /s h / in the /a/ context was perceived as an aspirated affricate in 73% of trials. To further investigate whether the 3 groups here perceived aspiration in the stimuli differently, each response was coded as either aspirated or unaspirated based on the Mandarin category chosen as most similar to the stimulus.…”
Section: Perceptual Assimilationsupporting
confidence: 75%
See 4 more Smart Citations
“…This result for the NM group replicates Holliday (2014a), who found that /s h / in the /a/ context was perceived as an aspirated affricate in 73% of trials. To further investigate whether the 3 groups here perceived aspiration in the stimuli differently, each response was coded as either aspirated or unaspirated based on the Mandarin category chosen as most similar to the stimulus.…”
Section: Perceptual Assimilationsupporting
confidence: 75%
“…It was expected that either the second or the third hypothesis would be supported, although if the results supported the second hypothesis it would need to be explained why the L2 learners were unable to map the acoustic cues to the /s h /-/s*/ contrast onto the appropriate category labels. The third hypothesis represented the most straightforward explanation of Holliday (2014a) and Holliday (2014b). In addition, the current study also tested the /s h /-/s*/ identification accuracy of novice and advanced L1 Mandarin learners of Korean using CVs produced in isolation, to see whether the poor performance of the L1 Mandarin listeners in Holliday (2014b) could have been because the stimuli were CVs extracted from longer words.…”
Section: L2mentioning
confidence: 99%
See 3 more Smart Citations